Statistics about U.S. special ops, past and present - Larson, Kirsten W (North Mankato, Minnesota Capstone Press, a capstone imprint, 2017)
"Details the history of U.S. Special Operations with the help of statistics"--
The world around us
Includes bibliographical references (page 47) and index
1 2 13 15
Keywords: Special forces (Military science) -- Juvenile literature; Special operations (Military science) -- United States -- History -- Juvenile literature